2018
DOI: 10.1111/pde.13726
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of topical therapy combined with 308‐nm excimer laser on vitiligo compared to excimer laser monotherapy in pediatric patients

Abstract: We evaluated the efficiency of using a 308‐nm excimer laser with either tacrolimus, pimecrolimus, or halometasone for the treatment of childhood vitiligo. Patients who received combined treatments had significantly higher rates of repigmentation in comparison with individuals who underwent excimer laser alone therapy. Moreover, patients who received treatment with excimer laser and halometasone had significantly higher rates of repigmentation, even higher than individuals who were treated with tacrolimus combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…It has the characteristics of repeated attacks and a long treatment cycle, and has become one of the main skin diseases perplexing clinical medical staff and patients (12). Halometasone cream, as a common topical glucocorticoid, has good physiological anti-inflammatory functions, including inhibition of epidermal hyperplasia and immune control, but it has some dosage and location limitations (13). Traditional Chinese medicine has a long history and good curative effect in the treatment of eczema with little side effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has the characteristics of repeated attacks and a long treatment cycle, and has become one of the main skin diseases perplexing clinical medical staff and patients (12). Halometasone cream, as a common topical glucocorticoid, has good physiological anti-inflammatory functions, including inhibition of epidermal hyperplasia and immune control, but it has some dosage and location limitations (13). Traditional Chinese medicine has a long history and good curative effect in the treatment of eczema with little side effects.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, therapies that promote melanogenesis and melanocyte proliferation have been considered as the most promising treatment methods for vitiligo. 5 308-nm excimer laser is monochromatic light at a specific wavelength and is formed by dimerides of xenon (8 electrons at the outmost layer) and chlorine (7 electrons at the outmost layer) after activation and continuous pulsatile release under the action of electric current. 6 In 2001, Baltás and Nagy utilized 308-nm excimer laser in the treatment of vitiligo for the first time, and definite treatment effect was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…4 The promotion of melanocyte proliferation and melanogenesis enhancement is, therefore, a prospective vitiligo therapeutic strategy. 5 Indeed, for the management of various skin disorders, the 308-nm excimer laser has become a common strategy. 6 It has also been revealed that this laser has been used successfully to treat vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal loss of melanin outcomes in vitiligo‐related pathological procedures . The promotion of melanocyte proliferation and melanogenesis enhancement is, therefore, a prospective vitiligo therapeutic strategy . Indeed, for the management of various skin disorders, the 308‐nm excimer laser has become a common strategy .…”
Section: Introductionmentioning
confidence: 99%